2020
DOI: 10.1007/s10973-020-09858-7
|View full text |Cite
|
Sign up to set email alerts
|

The potential of biocarbon as CO2 adsorbent in VPSA unit

Abstract: The best solution to the main environmental problem seems to be CO2 capture to reduce greenhouse gas emissions. The activated carbons derived from biomass have attracted extensive attention as solid adsorbent for carbon dioxide capture process. In this work, we focus on examining the properties of biochar (non-activated porous carbon) produced from biomass. Physicochemical properties of the biochar were investigated by thermogravimetric analysis (TG), Fourier transform infrared spectroscopy, scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A combination of the PSA and VSA processes, denoted as the VPSA process, has attracted much attention; its adsorption step is performed at above atmospheric pressure, and its desorption step is performed under vacuum. Izabela and Marcelina 77 reported that engineered biochar-based adsorbents, even with poor CO 2 uptake in sample-level CO 2 adsorption, achieved high CO 2 working capacities in a VPSA process. They also tested biomass-based carbonaceous materials in this VPSA process, highlighting their potential as practical CO 2 adsorbents for commercial CO 2 capture.…”
Section: Cyclic Performance Evaluation For Post-combustion Co2 Capturementioning
confidence: 99%
“…A combination of the PSA and VSA processes, denoted as the VPSA process, has attracted much attention; its adsorption step is performed at above atmospheric pressure, and its desorption step is performed under vacuum. Izabela and Marcelina 77 reported that engineered biochar-based adsorbents, even with poor CO 2 uptake in sample-level CO 2 adsorption, achieved high CO 2 working capacities in a VPSA process. They also tested biomass-based carbonaceous materials in this VPSA process, highlighting their potential as practical CO 2 adsorbents for commercial CO 2 capture.…”
Section: Cyclic Performance Evaluation For Post-combustion Co2 Capturementioning
confidence: 99%
“…However, by 2040 more than 2500 large-scale CCS/CCU facilities are required to limit climate change to 2℃ (11)(12)(13). The methods of post-combustion carbon capture include adsorption by solid materials and aqueous (14) along with afforestation and in situ injection and storage of carbon in the form of treated biomass (biocarbon/biochar). The adsorption methods are less energyintensive as well as avoid the production of contaminated sorbents and adverse byproducts (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The methods of post-combustion carbon capture include adsorption by solid materials and aqueous (14) along with afforestation and in situ injection and storage of carbon in the form of treated biomass (biocarbon/biochar). The adsorption methods are less energyintensive as well as avoid the production of contaminated sorbents and adverse byproducts (14,15). Consequently, carbon balance not only in the terrestrial ecosystem but also in the entire ecosystem by 2050 would be the key to mitigating global climate changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is not surprising that recent times have seen a rise in interest regarding CO 2 capture and separation. The studies explore various physical and chemical methods of adsorption of CO 2 into solids ,,, or absorption into liquids. Liquid technologies are already well-established and applied in industry, yet it has been suggested that further development is needed. ,, The main issues are the energy consumption of regeneration, running costs coming from evaporation, and the environmental impact of the solvents used. , Solid adsorbents have the potential to be less energy demanding and more efficient compared to liquids . Solid monomeric, oligomeric, or polymeric adsorbents, ,,, polymer membranes, , and hybrid systems ,,, are being developed to solve the issues with conventional liquid systems to allow lower regeneration temperatures, the avoidance of solvents, and an increase in the active surface area for more sustainable and efficient systems.…”
Section: Introductionmentioning
confidence: 99%